Medical Model in Caries Management - Madeline Jun Yu Yon; Sherry Shiqian Gao; Kitty Jieyi Chen; Duangporn Duangthip; Edward Chin Man Lo; Chun Hung Chu (Dentistry Journal, 2019)
The current mode of dental caries management mainly operates through irreversible and symptomatic treatment by means of drilling and filling, while caries prevention is largely overlooked or omitted. Focus should be redirected through a medical model towards elimination of the disease through tackling its causes and risk factors to address current and future caries initiation. Caries is the demineralisation of dental hard tissues by bacterial acids when periodically exposed to fermentable carbohydrates. The medical model of caries management is a philosophy that steers sustainable caries management through controlling bacterial infection, a reduction of risk levels, remineralisation of teeth and long-term follow-up. Its goal is to prevent new and recurrent caries, arrest ongoing caries processes by alteration of the cariogenic environment, and support the healing of remineralisable enamel and dentine. The mechanism involves dietary counselling and plaque control, placement of dental sealants, administration of fluoride agents and chemotherapeutic medications and use of chewing gum. This paradigm shift from a surgical to a medical model aims to pursue the ultimate intention of maintaining a caries-free dentition and is anticipated to promote true oral health-related quality of life. The objective of this paper is to discuss the medical model of caries management.